Enrichment factors for clinical trials in mild‐to‐moderate Alzheimer's disease - Clive Ballard; Alireza Atri; Neli Boneva; Jeffrey L. Cummings; Lutz Frölich; José Luis Molinuevo; Pierre N. Tariot; Lars Lau Raket (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Heterogeneity of outcomes in Alzheimer's disease (AD) clinical trials necessitates large sample sizes and contributes to study failures. This analysis determined whether mild‐to‐moderate AD populations could be enriched for cognitive decline based on apolipoprotein (APOE) ε4 genotype, family history of AD, and amyloid abnormalities. Methods Modeling estimated the number of randomized patients needed to detect a 2‐point treatment difference on the AD Assessment Scale–Cognitive subscale using placebo data from three randomized, double‐blind trials (ClinicalTrials.gov Identifiers: NCT01955161, NCT02006641, and NCT02006654). Results An 80% power to detect a 2‐point treatment effect required the randomization of 148 amyloid‐positive patients; 178 ε4 homozygous or amyloid‐positive patients; and 231 ε4 homozygous, family history‐positive, or amyloid‐positive patients, compared with 1619 unenriched patients (per arm). Discussion Enrichment in mild‐to‐moderate AD clinical trials can be achieved using combinations of biomarkers/risk factors to increase the likelihood of observing potential treatment effects.